MED28 over-expression shortens the cell cycle and induces genomic instability - Cho, Jin Gu; Choi, Joon Seok; Lee, Jae Ho; Cho, Min Guk; Kim, Hong Sook; Noh, Hee Dong; Lim, Key Hwan; Park, Byoungjun; Kim, Jin Ock; Park, Sang Gyu (International Journal of Molecular Sciences, 2019)
The mammalian mediator complex subunit 28 (MED28) is overexpressed in a variety of cancers and it regulates cell migration/invasion and epithelial-mesenchymal transition. However, transcription factors that increase MED28 expression have not yet been identified. In this study, we performed a luciferase reporter assay to identify and characterize the prospective transcription factors, namely E2F transcription factor 1, nuclear respiratory factor 1, E-26 transforming sequence 1, and CCAAT/enhancer-binding protein β, which increased MED28 expression. In addition, the release from the arrest at the G1−S or G2−M phase transition after cell cycle synchronization using thymidine or nocodazole, respectively, showed enhanced MED28 expression at the G1−S transition and mitosis. Furthermore, the overexpression of MED28 significantly decreased the duration of interphase and mitosis. Conversely, a knockdown of MED28 using si-RNA increased the duration of interphase and mitosis. Of note, the overexpression of MED28 significantly increased micronucleus and nuclear budding in HeLa cells. In addition, flow cytometry and fluorescence microscopy analyses showed that the overexpression of MED28 significantly increased aneuploid cells. Taken together, these results suggest that MED28 expression is increased by oncogenic transcription factors and its overexpression disturbs the cell cycle, which results in genomic instability and aneuploidy.
Keywords: Aneuploidy; Cell Cycle; Genomic Instability; HEK293 Cells; HeLa Cells; Humans; MCF-7 Cells; Mediator Complex; Nocodazole; Promoter Regions, Genetic; Thymidine; Transcription Factors; Up-Regulation; Aneuploidy; Cell cycle; Micronucleus; Nuclear budding; Transcription factor